INCREASED SERUM LEVELS OF UREA AND CREATININE ARE SURROGATE MARKERS FOR DISRUPTION OF RETINAL PHOTORECEPTOR EXTERNAL LIMITING MEMBRANE AND INNER SEGMENT ELLIPSOID ZONE IN TYPE 2 DIABETES MELLITUS - Saxena, Sandeep; Ruia, Surabhi; Prasad, Senthamizh; Jain, Astha; Mishra, Nibha; Natu, Shankar M; Meyer, Carsten H; Gilhotra, Jagjit S; Kruzliak, Peter; Akduman, Levent (Retina, 2017)
PURPOSE: To evaluate the role of serum urea and creatinine as surrogate markers for disruption of retinal photoreceptor external limiting membrane (ELM) and inner segment ellipsoid zone (EZ) in Type 2 diabetic retinopathy (DR) using spectral-domain optical coherence tomography, for the first time. METHODS: One hundred and seventeen consecutive cases of Type 2 diabetes mellitus (diabetes without retinopathy [No DR; n = 39], nonproliferative diabetic retinopathy [NPDR; n = 39], proliferative diabetic retinopathy [PDR; n = 39]) and 40 healthy control subjects were included. Serum levels of urea and creatinine were assessed using standard protocol. Spectral-domain optical coherence tomography was used to grade the disruption of ELM and EZ as follows: Grade 0, no disruption of ELM and EZ; Grade 1, ELM disrupted, EZ intact; Grade 2, ELM and EZ disrupted. Data were analyzed statistically. RESULTS: Increase in serum levels of urea (F = 22.93) and creatinine (F = 15.82) and increased grades of disruption of ELM and EZ (γ = 116.3) were observed with increased severity of DR (P < 0.001). Increase in serum levels of urea (F = 10.45) and creatinine (F = 6.89) was observed with increased grades of disruption of ELM and EZ (P = 0.001). CONCLUSION: Serum levels of urea and creatinine are surrogate markers for disruption of retinal photoreceptor ELM and EZ on spectral-domain optical coherence tomography in DR.
Keywords: dospělí; studie případů a kontrol; Humans; Analysis of Variance; Creatinine; Photoreceptor Cells, Vertebrate; lidé středního věku; nemoci retiny; Middle Aged; Retinal Diseases; mužské pohlaví; diabetes mellitus 2. typu; močovina; epiretinální membrána; Severity of Illness Index; stupeň závažnosti nemoci; Epiretinal Membrane; Adult; Diabetic Retinopathy; Retinal Photoreceptor Cell Inner Segment; vnitřní segment fotoreceptoru sítnice; biologické markery; analýza rozptylu; diabetická retinopatie; ženské pohlaví; Diabetes Mellitus, Type 2; fotoreceptory obratlovců; lidé; Case-Control Studies; kreatinin; Urea; Biomarkers; Aged; senioři; Male; Female